Policy Implementation For Community Empowerment In Southeast Maluku District - Selanno, Henry; Rahawarin, Mohamad Arsad; Madun, Hikmawaty (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to analyze (1) the implementation of community empowerment policies through poverty alleviation, (2) the effectiveness of community empowerment policy implementation through poverty alleviation in terms of the aspects of policy accuracy, implementation accuracy, target accuracy, environmental accuracy and process accuracy, (3 ) factors that influence the implementation of community empowerment policies through poverty alleviation and (4) community empowerment policy strategies through poverty alleviation. Data were analyzed using qualitative analysis. The results of the study concluded that (1) the policy of community empowerment through poverty alleviation has been translated through various work programs prepared by the Regional Poverty Management Coordination Team (TKPKD) whose members are regional work units (SKPD) which later become regional apparatus organizations (OPD); (2) The implementation of community empowerment policies through handling poverty has not been maximized in terms of policy accuracy, implementation accuracy, target accuracy, environmental accuracy and process accuracy; (3) Factors that influence the implementation of community empowerment policies through poverty alleviation are policy errors, distribution of social assistance and weak data accuracy and (4) Community empowerment policy strategies through poverty alleviation are focused on political will and institutional dimensions, both dimensions of policy content and three dimensions policy environment.